The Effectiveness of TikTok Videos to Enhance Students’ Motivation and Speaking Skills - Setiowati; Issy Yuliasri; Abdrurrachman Faridi (English Education Journal, 2024)
Speaking skills are one of the most important skills in English language learning. However, most students, especially at SMPN 1 Cepu, still lack self-confidence, have limited vocabulary, are passive in learning, and need to be more active in using English in daily conversations. This research implemented TikTok videos integrated into project-based learning. This research aims to determine the effectiveness of using TikTok in improving students’s motivation and speaking skills. This research includes a mixed-method type, quasi-experiment research design (quantitative research – t-test) and (qualitative research – interview and questionnaire). Statistical test to determine whether there is an influence of using TikTok videos on speaking skills through an independent sample t-test using SPSS 24. Meanwhile, a statistical test to determine whether there is an influence of using TikTok on student motivation is the Mann-Whitney test. Based on the results of statistical tests, an Asymp Sig (2-tailed) value of 0.001 or less than 0.05. This means that Ha is accepted. This means that there is an average difference between the experimental and control classes. There is a significant difference in the average score of speaking skills between the experimental class and the control class. Apart from that, there was a significant difference in the average motivation score between the experimental class and the control class. The implication of this research is TikTok can be used as a learning media that can motivate students and improve speaking skills.